Respuestas
Respuesta dada por:
0
(a + b)² = a² +ab +ba + b² (a + b)² = a² + 2ab + b² (a - b)² = a² -ab -ba + b² (a - b)² = a² - 2ab + b² Ej: (2 + √2)² = 2² + 2×2√2 + (√2)² (2 + √2)² = 4 + 4√2 + 2 (2 + √2)² = 6 + 4√2
Respuesta dada por:
1
1. (2 + x)² = 2² + 2(2)(x) + x²
= 4 + 4x + x²
2. (3a – 5b)² = (3a)² - 2(3a)(5b) + (5b)²
= 9a² - 30ab + 25b²
5. (x + y)² = x² + 2 (x)(y) + y²
= x² + 2xy + y²
6. (p - q)² = p² - 2pq + q²
7. (2p + q)² = (2p)² + 2(2p)(q) + q²
= 4p² + 4pq + q²
8. (3a + b)² = (3a)² + 2(3a)(b) + b²
= 9a² + 6ab + b²
9. (2a - 3b)² = (2a)² - 2(2a)(3b) + (3b)²
= 4a² - 12ab + 9b²10. (x + 1)² = x² + 2(x)(1) + (1)²
= x² + 2x + 1
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años